Down in the garden - Geddes, Anne (San Rafael, CA Cedco Pub., 1996)
Full color photographs featuring babies and toddlers in various costumes and dress depicting garden scenes.
New Zealand photographer.
Originally published: Auckland, N.Z. : Hodder Moa Beckett, 1996.
112122
Keywords: Down in the garden; Photography of infants; Infants -- Pictorial works; Babies -- Pictorial works; Children -- Portraits; Animals in art; Plants in art; illustrated books; Illustrated works